The Effect of Stir-Squeeze Casting Process Parameters on Mechanical Property and Density of Aluminum Matrix Composite - S. Vijayakumar; P. S. Satheesh Kumar; Pappula Sampath kumar; Selvaraj Manickam; Gurumurthy B. Ramaiah; Hari Prasadarao Pydi (Advances in Materials Science and Engineering)
This present investigation focusing on preparation of Al-based hybrid composites in which Al6082 is engaged as the main alloy reinforced with two reinforcements of ZrSiO₄/TiC. The combination of the stir-squeeze process helps to make different specimen by change of four parameters such as stir speed, stir time, reinforcements, and squeeze pressure. In this process, two reinforcements are reserved as constant about 7.5 wt%. The four levels of each parameter are stir speed (300, 400, 500, and 600 rpm), stir time (10, 15, 20, and 25 min), reinforcement (2.5, 5, 7.5, and 10 wt%), and squeeze pressure (50, 60,70, and 80 MPa). According to the L16 orthogonal array Taguchi design, the specimens are created to analyze the mechanical properties of tensile strength and hardness along with porosity. In addition, the optimization technique is used to determine the optimal parameter on improving tensile strength. The optimization process can be assisted by the software namely Minitab-17 which helps to study analysis of variance, regression model, and contour plots. The observed result of ANOVA showed that stir speed (41.8%) is the maximum influenced parameter that increases TS, followed by squeeze pressure (25.7%), stir time (12.7%), and reinforcement (1.96%), and optimum tensile strength is found at the parameters of stir speed 600 rpm, stir time 10 min, reinforcement 2.5 wt%, and squeeze pressure 80 MPa. The fractured surface of tensile strength also examined by the SEM test. The combined parameters of S4-T1-R1-P4 achieve the highest TS, and it is observed that there are nearly no pore defects and good diffusion as a result of the reinforcements to be properly mixed. It is noticeable that the TiC and Al 6082 matrix, as well as the various ZrSiO4 exhibit stronger bonds.